Una nota acerca de los subsidios, la política y la economía - Castillo, José Gabriel (2020)
A scary issue regarding the efficiency of public management in Ecuador is related to fuel subsidies. Many years go by without making serious decisions on the subject and each time it is encountered or debated on the table, it becomes the first pretext for our fragile democracy to falter; Look at what happened in the governments of Bucaram, Jamil Mahuad and Gustavo Noboa. In the current government structure, dependent on an ambitious plebiscitary dynamic and with a state administration scheme still in the making, things are not different and the issues in which the slightest political cost is perceived are left aside in favor of maintain popularity in an electoral campaign that today seems to be eternal. In Ecuador the legislative task in this matter has also been postponed for a period of around 30 years.